Failure of Translation of Human Adenovirus mRNA in Murine Cancer Cells Can be Partially Overcome by L4-100K Expression In Vitro and In Vivo - Young, Anna-Mary (Nature Publishing Group, 2012)
Adaptive immune responses may be vital in the overall efficacy of oncolytic viruses in human malignancies. However, immune responses to oncolytic adenoviruses are poorly understood because these viruses lack activity in murine cells, which precludes evaluation in immunocompetent murine cancer models. We have evaluated human adenovirus activity in murine cells. We show that a panel of murine carcinoma cells, including CMT64, MOVCAR7, and MOSEC/ID8, can readily be infected with human adenovirus. These cells also support viral gene transcription, messenger RNA (mRNA) processing, and genome replication. However, there is a profound failure of adenovirus protein synthesis, especially late structural proteins, both in vitro and in vivo, with reduced loading of late mRNA onto ribosomes. Our data also show that in trans expression of the nonstructural late protein L4-100K increases both the amount of viral mRNA on ribosomes and the synthesis of late proteins, accompanied by reduced phosphorylation of eIF2α and improved anticancer efficacy. These results suggest that murine models that support human adenovirus replication could be generated, thus allowing evaluation of human adenoviruses in immunocompetent mice.